LEVERAGE AND FIRM SIZE ON FIRM VALUE IN LQ45 COMPANIES - Laynita Sari; Fuji Rahayu Ningtia; Dewi Zulvia; Mike Kusuma Dewi (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze the effect of leverage and firm size on firm value in LQ45 companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Firm value in this study is measured using Price to Book Value (PBV). This research uses a quantitative approach with secondary data obtained from the annual financial statements of LQ45 companies published on the official website of the Indonesia Stock Exchange. The sampling technique used purposive sampling, resulting in 27 companies with a total of 108 observation data. Data analysis was conducted using panel data regression analysis with the assistance of EViews software. The results indicate that leverage has a positive but insignificant effect on firm value, while firm size has a negative and significant effect on firm value. These findings indicate that the use of debt has not been able to significantly increase investor confidence in company performance, while larger company size tends to reduce firm value due to inefficiency and increasing operational complexity.